A Cloud based Assurance Framework for Implementation of ERP in SMEs: A Literature Survey - Mehta, Sunaina; Oberoi, Ashish; Bhatia, Sarvjit Singh (International Journal of Computer Sciences and Engineering, 2025)
Enterprise Resource Planning (ERP) system is an integral component of IT infrastructure in many organizations. They are the vital asset to any organization in carrying out various operational tasks with greater reliability and efficiency. Most of the Indian SMEs have adopted the traditional ERP systems and have incurred heavy cost while implementing these systems. Cloud computing has changed the era of doing the business in the global market. SMEs will not have to invest more for the implementation of cloud ERP they can utilize the resources as a service and pay as per their usage. Cloud ERP is nothing more than ERP software that had been implemented on cloud. This paper present to review a deeper understanding of Cloud ERP , emerging technologies such as Cloud Computing , Software as Service (SaaS), to frame the multi-tenant assured framework which are more relevant and beneficial for SMEs.